Help-Seeking Behaviors and Mental Well-Being of Albanian Immigrants in Malaysia - Thartori, Voltisa; Hisham Ismail, Nik A.; Idrus, F.; Kassim, S.K. (2023)
The objective of this study is to explore the life experiences of 18 ethnic Albanian immigrants from Albania and Kosovo currently living in Malaysia or who’d previously lived in Malaysia and currently live in Australia. Specifically, the study explores (i) the obstacles and barriers immigrants face in Malaysia and (ii) the role stigmatization has had regarding the immigrants’ help-seeking behaviors. The study uses the phenomenological case study design and in-depth semi-structured interviews for collecting the data. The results show that narrations regarding phenomena such as cultural shock, permanent residence status, stigmatization toward the immigrants, and being labeled with terms such as Mat Salleh [Westerners] have adversely affected the immigrants’ mental well-being. In addition, the Albanian immigrants, especially the females, felt safer confiding their burdens and challenges with family members and close friends. Negative perceptions, stigmatization, and labeling are among the psychological explanations the Albanian immigrants experienced. These inevitable shortfalls affect the immigrants’ mental well-being and correspond similarly to the experiences of many immigrants all over the world.